Antropogeniczny świat „zbędnego człowieka” bohatera emigracyjnych trylogii Eduarda Limonowa - Bieliński, Robert (My University, 2010)
Osobowość Ediczki w świetle przeprowadzonej analizy na podstawie trylogii amerykańskiej (To ja – Ediczka, Dziennik nieudacznika, Historia jego sługi) oraz trylogii rosyjskiej (Mieliśmy Wielką Epokę, Wyrostek Sawienko, Młody niegodziwiec) ma dwa wymiary: natura pisarza splata się z cechami charakteru, dzięki którym zostają mu przypisane epitety typu: niegodziwiec, awanturnik, skandalista. Nie odnalazłszy stałego miejsca w życiu, nieustannie biegnie w poszukiwaniu własnej przystani i własnej przestrzeni. Świat otaczającej go antroposfery nie spełnia jego wygórowanych oczekiwań. Ediczka jest inny i tą oryginalnością, swoistością chce olśnić wszystkich. Niezależnie od miejsca i czasu brnie ku światłu, które jak magnes go przyciąga. Znamiennym jest ciągły ruch w życiu bohatera lub pragnienie zmian. Ediczka kreuje wówczas nową antroposferę, swój własny świat, swoje miejsce, w którym czuje się sobą. Bytuje w nim, bo tylko tu jest mu tak naprawdę dobrze. Żyje sam, z dala od tłumu. swoim bytem bohater Limonowa przypomina taniec chocholi, wielki zastój. W latach dzieciństwa skazany na takie życie, czyli życie w ZSRR, widzi, czym taka egzystencja się kończy. W życiu ludzi radzieckich lat 70-tych brak jest celu, praca stanowi obowiązek i nie przynosi satysfakcji.

Eddie’s personality in the light of conducted analysis based on the American trilogy (It’s me – Eddie, Loser’s daily, History of his servant) and on Russian trilogy (We had the Great Age, Sawienko Stripling, Young rogue) has two dimensions: writer’s nature is intertwining with character traits, thanks to which epithets are ascribed to him, like: rogue, troublemaker, scandalous man. Not having found the permanent place in the life, he is running incessantly in quest his own harbour and his own space. World of surrounding him antroposphere isn't meeting his excessive expectations. Eddie is different and with this otherness he wants to dazzle everyone. Irrespective of the place and the time he is wading towards the light which is pulling him like the magnet. Characteristic is continuous movement in character’s life or changes desire. Eddie is creating then new antrophosphere, his own world. In the life of Soviet 70s people there is no aim, work constitutes the obligation and it brings no satisfaction. Eddie isn't accepting anthroposphere like this, this human exists. He is rejecting it firmly, renounce the same time his family house, and friends. Eddie seemingly isn't other from his peers, but however he is different– he is making poems up, he is reading west literature. He is starting also writing the prose. Eddie lives on approval, he is struggling with the time and space, tried to find real of himself in this way. He is never making a success of it. Every new antrophosphere is rejecting him, it doesn't want him. Ediczka is suffering, but thanks to that he exists and he is noticed.
Anthropogenic world of „ unnecessary man” - character in Eduard Limonov's emigrational trilogies
Wydział Neofilologii: Instytut Filologii Rosyjskiej
Keywords: Zbędny człowiek; Unnecessary man; antroposfera; antrophosphere; Ediczka; Eddie; Limonov; Limonow